1991
DOI: 10.1346/ccmn.1991.0390101
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopic Study of the Kaolinitization of Muscovite

Abstract: Abstract--Hydrothermally kaolinitized muscovite from the Otago schist of Brighton, New Zealand, has been studied by transmission and analytical electron microscopy (TEM and AEM) to determine the mechanism of alteration and to compare reactant-product relations for di-and trioctahedral micas. The muscovite is a primary metamorphic phase having a phengitic composition. It occurs as well-ordered, two-and three-layer polytypes, in grains as thick as 30 tim. Kaolinite occurs as packets of layers, each about 100-600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…This Fe-Mg chlorite is inferred to be a primary hydrothermal, pre-metamorphic product that originated during ore-forming processes, or a metamorphic phase that evolved from possible hydrothermal precursors such as smectite and mixed-layer chlorite/smecdte. The presence of hybrid phases usually is suggested to result from retrograde metamorphic or hydrothermal reactions under non-equilibrium conditions (e.g., Banfield et al, 1989;Jiang and Peacor, 1991). The complex, heterogeneous mixed-layer chlorite/berthierine, berthierine, and Fe-rich chlorite in sample KC-2505 have properties that are consistent with non-equilibrium states and, therefore, are likely alteration products of homogeneous Fe-Mg chlorite formed earlier.…”
Section: Alteration Of Chlorite To Berthierinementioning
confidence: 98%
See 2 more Smart Citations
“…This Fe-Mg chlorite is inferred to be a primary hydrothermal, pre-metamorphic product that originated during ore-forming processes, or a metamorphic phase that evolved from possible hydrothermal precursors such as smectite and mixed-layer chlorite/smecdte. The presence of hybrid phases usually is suggested to result from retrograde metamorphic or hydrothermal reactions under non-equilibrium conditions (e.g., Banfield et al, 1989;Jiang and Peacor, 1991). The complex, heterogeneous mixed-layer chlorite/berthierine, berthierine, and Fe-rich chlorite in sample KC-2505 have properties that are consistent with non-equilibrium states and, therefore, are likely alteration products of homogeneous Fe-Mg chlorite formed earlier.…”
Section: Alteration Of Chlorite To Berthierinementioning
confidence: 98%
“…Specimen preparation and instrumental settings were detailed in Jiang and Peacor (1991) and Slack et al (1992). A selected area aperture 10 #m in diameter was utilized to produce the electron diffraction patterns.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Kaolinite, like berthierine, has d(001) 7 /~, and these minerals can therefore be distinguished from each other only with difficulty. Kaolinite is especially difficult to identify by TEM methods since it is rapidly damaged by interaction with the electron beam and becomes amorphous within a few seconds (Jiang and Peacor 1991). Curtis et al (1984,1985) concluded that the presence of alkalis in their analyses implied contamination by admixed illite or residual smectite.…”
Section: Analytical Electron Microscope Analyses Of Chlorite New Analmentioning
confidence: 99%
“…Preparation of TEM specimens was detailed in Jiang and Peacor (1991). Carbon-coated, ion-milled TEM specimens were first studied by optical microscopy and scanning electron microscopy (SEM) to identify largescale textural relations and to locate areas of interest for TEM observations.…”
Section: Materials and Experimental Techniquesmentioning
confidence: 99%